Electric-Field Control of Spin-Orbit Torques in Perpendicularly Magnetized W/CoFeB/MgO Films - Filianina, Mariia; Hanke, Jan-Philipp; Lee, Kyujoon; Han, Dong-Soo; Jaiswal, Samridh; Rajan, Adithya; Jakob, Gerhard; Mokrousov, Yuriy; Klaeui, Mathias (Physical Review Letters, 2020)
Controlling magnetism by electric fields offers a highly attractive perspective for designing future generations of energy-efficient information technologies. Here, we demonstrate that the magnitude of current-induced spin-orbit torques in thin perpendicularly magnetized CoFeB films can be tuned and even increased by electric-field generated piezoelectric strain. Using theoretical calculations, we uncover that the subtle interplay of spin-orbit coupling, crystal symmetry, and orbital polarization is at the core of the observed strain dependence of spin-orbit torques. Our results open a path to integrating two energy efficient spin manipulation approaches, the electric-field-induced strain and the current-induced magnetization switching, thereby enabling novel device concepts.
CRIS-Team Scopus Importer:2023-03-27